The Manufacture of printed circuit boards - Ables, Amher A.; Dalanon, Joy M.; Luyun, Rochelle A.; Rodriguez, Jocelyn A. (College of Engineering, 1999)
Product: Printed circuit boards -- Company name: CircuitMasters -- Capacity: 82,540 kg/yr (96,155 sq. m/yr) -- Selling price: Php 18,00/sq.m -- Total capital investment: Php 389,955,794.00 -- Total product cost: Php 1,495,757,496 -- Return on investment: 23.82% -- Payback period: 4.2 years -- Plant location: Carmelray I, Canlubang, Laguna